Winter range drift in the George River Caribou Herd: a response to summer forage limitation? - Schmelzer, Isabelle; Otto, Robert (Rangifer, 2003)
Space use by the George River caribou herd (GRCH) changes in correspondence with migration patterns. The traditional range of this herd encompasses an area of approximately 900 000 km2. Range use is seasonal and includes travel to traditional calving grounds. Winter range use however, is more variable. The GRCH has grown rapidly from 5000 animals in 1954 to approximately 775 000 in 1993. Beginning in the mid 1980s, the calving and summer range habitats of the GRCH have deteriorated, resulting in a decline in physical condition and subsequent poor calf survival and low pregnancy rates. We assessed the importance of the winter range as a food source compensating for poor summer range quality through an evaluation of winter range drift and use intensity. We hypothesized that if winter ranges provide a compensatory source of forage, then George River caribou should avoid sites heavily used during the previous winter at a population level. Winter ranges for the GRCH were calculated using 4300 caribou locations obtained 1986-2000. We found that in spite of a doubling in net range area, the size of annual winter ranges did not increase, indicating the occurrence of range drift. Further, George River caribou exhibited avoidance of wintering areas at several spatial scales. Avoidance occurred across a use threshold, where the degree of use (or density) during the previous winter determined the level of avoidance during the subsequent winter. As the spatial scale decreased, the degree of avoidance increased. Caribou significantly avoided areas used the previous winter at spatial scales below and including 245 km2 (corresponding to a 75% use distribution). Results suggest winter foraging allows caribou suspend the effects of density-dependent summer forage limitation on herd productivity. As such, analysis of GRCH population trends should be considered in light of both summer and winter range resources.